IMPLEMENTASI KEBIJAKAN PEMBUATAN SERTIFIKAT TANAH DI KABUPATEN KEPULAUAN TALAUD - ESSING, REKLI; LALOMA, ALDEN; PLANGITEN, NOVVA (Sam Ratulangi University, 2018)
bstract: The aim of this research is to know the implementation of policy of land certificate in Talaud Islands Regency asthe executor of KanTah of Talaud Islands Regency. Larasita is a policy issued by BPN RI in order to maximize services inthe field of land is making land certificate by doing direct service to the community. Number of informants 6 people. Thisresearch uses descriptive qualitative research type that is a method to describe a social phenomenon or trying to describecertain social phenomena in detail. This research was conducted at the land office of talaud islands district on 14 - 18 May2018. In the research, to know about the implementation of policy, the writer uses theory from Edwad III where there arefour factors influencing it, namely Communication, Resources, disposition and bureaucratic structure. The result of theresearch shows that the policy of larasita in the district land office. Talaud islands are not implemented because there is nosocialization done by the implementing party to the community, lack of human resources consisting of only 9 ASN and 9PTT, no breakthroughs and positive ideas to improve the service of land certificate (larasita), the last is lack of coordinationamong policy implementing units.Keywords: Policy Implementation, Land Certificate